2023
DOI: 10.1021/acsnano.3c00600
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-Induced Colloidal Encapsulation for Probiotic Oral Delivery

Abstract: Probiotic oral delivery has crucial implications in biomedical engineering, but its oral bioavailability remains unsatisfactory because of the limited survival and colonization of probiotics in the harsh gastrointestinal tract. Here, a bacteria-induced encapsulation strategy is achieved by assembling metastable colloids to enhance the oral bioavailability of probiotics. The colloids (NTc) composed of amino-modified poly-β-cyclodextrin and tannic acid are formed based on the balance of host−guest interaction-dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Jia Lingyun et al used positively charged colloids (NTc) composed of amino-modified poly-β-cyclodextrin and tannic acid to encapsulate negatively charged probiotics, showing strong resistance to simulated gastric acid with a survival rate of up to 19%, which is 7500 times higher than that of the commercial enteric material L100. The encapsulated probiotics showed good therapeutic effects in a colitis mouse model [184]. Chen Qian et al utilized electrostatic self-assembly to encapsulate E. coli strains expressing catalase and superoxide dismutase with chitosan and sodium alginate as effective biofilms.…”
Section: In Vivo Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Jia Lingyun et al used positively charged colloids (NTc) composed of amino-modified poly-β-cyclodextrin and tannic acid to encapsulate negatively charged probiotics, showing strong resistance to simulated gastric acid with a survival rate of up to 19%, which is 7500 times higher than that of the commercial enteric material L100. The encapsulated probiotics showed good therapeutic effects in a colitis mouse model [184]. Chen Qian et al utilized electrostatic self-assembly to encapsulate E. coli strains expressing catalase and superoxide dismutase with chitosan and sodium alginate as effective biofilms.…”
Section: In Vivo Methodologiesmentioning
confidence: 99%
“…This is 7500 times higher than commercial entericcoated material L100. The oral availability of encapsulated probiotics increased by about five times compared to non-encapsulated probiotics [184].…”
Section: Other Techniquesmentioning
confidence: 96%
“…Han et al reported a SYTO-9-labeled bacteriabased probe that could be electrostatically encased in a colloidal shell composed of amino-modified poly-𝛽-cyclodextrin and tannic acid, which enhanced oral availability and prolonged the intestinal adhesion duration, showing by in vivo imaging. [164] Liu et al encapsulated GFP-expressing bacteria with a lipid membrane coating through interfacial supramolecular self-assembly [161] Copyright 2019, American Chemical Society. b) 18 F-FDS-assisted PET imaging of E. coli MG1655 in tumor-bearing mice.…”
Section: Bioimaging Of the Gut Microbiota And Intestine-associated Di...mentioning
confidence: 99%
“…reported a SYTO‐9‐labeled bacteria‐based probe that could be electrostatically encased in a colloidal shell composed of amino‐modified poly‐β‐cyclodextrin and tannic acid, which enhanced oral availability and prolonged the intestinal adhesion duration, showing by in vivo imaging. [ 164 ] Liu et al encapsulated GFP‐expressing bacteria with a lipid membrane coating through interfacial supramolecular self‐assembly to build a bacteria‐based probe, with abilities to fight against various harsh environments, such as gastric acid and antibiotics, as well as to visualize the colonization of bacteria in the intestinal tract in vivo via fluorescent imaging. [ 40 ] H. pylori is a bacterium with high adaptability in extreme environments and can cause different diseases, such as peptic ulcers, gastric ulcers, and gastric cancer.…”
Section: Applications Of Bacteria‐based Living Probesmentioning
confidence: 99%
“…Ultimately, probiotics show very limited bioavailability, and they can hardly function properly in the intestine. Therefore, it is of great significance for researchers to establish new probiotic delivery strategies that can improve the oral probiotics’ bioavailability and intestinal colonization rate. , …”
Section: Introductionmentioning
confidence: 99%